What do we know about the impacts of the next El Niño on agrifood systems? - Koo, Jawoo; Anderson, Weston (International Food Policy Research Institute, 2025)
As of June 2023, the U.S. National Oceanic and Atmospheric Administration (NOAA) declared that El Niño conditions were present and consensus existed among climate prediction centers that El Niño would likely persist from November 2023 to February 2024.